EVALUATION AND CHARACTERIZATION OF SLEEPINESS IN MEDICAL RESIDENTS (CIPEEX, 2025)
The purpose of the present study is to evaluate and characterize sleepiness in medical residents and its relationship with sleep deprivation and clinical decision-making, in addition to comparing the prevalence and effect of sleepiness among residents of different specialties. Three validated instruments were used: the Epworth Sleepiness Scale (ESS) to assess daytime sleepiness, the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality, and the Melbourne Decision-Making Questionnaire (MDMQ) to identify decision-making profiles. The questionnaires were applied before and after hospital shifts, allowing the analysis of variation in sleepiness throughout the day. The results showed a high prevalence of excessive sleepiness among residents, especially in specialties with night shifts. Sleep deprivation was associated with poorer sleep quality and reduced decision-making capacity. Despite sleepiness, residents maintained a vigilant decision-making pattern, possibly as a compensatory mechanism. It is concluded that excessive sleepiness negatively affects residents, especially those with more night shifts, and may compromise clinical decision-making. This suggests the need for measures to monitor and reduce risk factors, improve mental health and quality of life of professionals, and reassess workload.
Keywords: Residency; Medicine; Sleep deprivation; Decision-making